The Impacts of PM2.5 on Stock’s Earnings in China - Weige Huang (International Journal of Information Systems and Informatics, 2023)
The particulate matter 2.5 (PM2.5) is a serious air-pollutant emission which has caused serious risks to public health in China. The concerns could impact the decisions of people when they are choosing which companies to work and the decisions further affect the earnings of the companies. This is because people especially the ones with high skills have more choices and would like to choose to work in a company which is located in a city with less PM2.5 concentration and the companies with more high-skill people tend to perform better. That is, the earnings should be higher. This paper studies the impacts of PM2.5 concentration on earnings per share (EPS) of stocks in China market. We find that PM2.5 has positive impacts on EPS in the entire market and the impacts are larger for stocks headquartered in the northwest of China. Also, we find that there exist heterogeneous effects of PM2.5 on EPS. That is, the impacts of PM2.5 tend to increase with EPS.